2015
DOI: 10.1016/j.molimm.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of pro-inflammatory TNFα and IL-17 in periostin mediated collagen deposition: Potential role in liver fibrosis

Abstract: Background The pro-inflammatory cytokines, tumor necrosis factor (TNF)-α, and interleukin (IL)-17, have been implicated in the pathogenesis of liver fibrosis. In this study, we investigated the role of TNFα and IL-17 towards induction of profibrotic factor, periostin. Methods HepG2 cells were cultured and treated with inflammatory cytokines, TNFα and IL-17. Computational promoter sequence analysis of the periostin promoter was performed to define the putative binding sites for transcription factors. Transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 47 publications
(62 reference statements)
2
62
0
Order By: Relevance
“…Other authors also reported higher serum periostin levels in patients with acute or chronic hepatitis compared with controls; in the same study, periostin levels were well associated with TGF-b1 and TGF-b2 [9]. Taken together, the aforementioned experimental and human data [7][8][9][10], periostin may mediate hepatic steatosis, inflammation, and fibrosis.…”
Section: Periostin In Hepatic Metabolismmentioning
confidence: 54%
See 2 more Smart Citations
“…Other authors also reported higher serum periostin levels in patients with acute or chronic hepatitis compared with controls; in the same study, periostin levels were well associated with TGF-b1 and TGF-b2 [9]. Taken together, the aforementioned experimental and human data [7][8][9][10], periostin may mediate hepatic steatosis, inflammation, and fibrosis.…”
Section: Periostin In Hepatic Metabolismmentioning
confidence: 54%
“…Importantly, in vitro activation of human hepatoblastoma cells (HepG2) with the proinflammatory and profibrogenic cytokines TNF-a, IL-17, or both, enhanced the expression of periostin by 3.5-, 4.4-, or 13.3-fold, respectively, compared to untreated cells [10]. It seems that periostin may mediate the type I collagen disposition induced by TNF-a and IL-6, thereby resulting in fibrosis [10].…”
Section: Periostin In Hepatic Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation can also cause HSC activation and result in liver fibrosis. Products of the inflammatory cascade like: TNF-α, IL-6, IL-1β and COX-2 are elevated, independently of the etiology, in liver diseases (Amara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Levels of circulating TNFα are increased in patients with liver fibrosis and are associated with poor prognosis (Amara et al, 2015). Thus, any approaches that attenuate its production, receptor activation, or downstream signal transduction should inhibit HSC activation and its subsidiary events (Wu and Zern, 2000).…”
Section: Introductionmentioning
confidence: 99%